2008
DOI: 10.1029/2006wr005632
|View full text |Cite
|
Sign up to set email alerts
|

Regional channelized transport in fractured media with matrix diffusion and linear sorption

Abstract: [1] A regional-scale solute transport model with long-range flow channeling is used to study the effect of matrix diffusion and linear sorption on channelized transport. We start from a fracture-network-based block model to build up a large-scale flow and transport model with regional flow channeling, and then incorporate the processes of matrix diffusion and linear sorption. Regional-scale solute transport is then studied by applying the model to the fracture data set from Sellafield, England. The results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…15(c) and (h)), due to the concurrent channeling flow that stretches the plume front downstream. The enhanced spread of the plume is similar to the numerical result in Odén et al [71], who found that matrix diffusion in channelized transport causes an increased spread in regional-scale fractured media. The persistent non-Fickian transport due to the long-term competition between the strong channeling and sequestration is reflected by the non-zero skewness and kurtosis ( Fig.…”
Section: Influence Of Hydrofacies Properties On Plume Snapshots and Ssupporting
confidence: 82%
See 1 more Smart Citation
“…15(c) and (h)), due to the concurrent channeling flow that stretches the plume front downstream. The enhanced spread of the plume is similar to the numerical result in Odén et al [71], who found that matrix diffusion in channelized transport causes an increased spread in regional-scale fractured media. The persistent non-Fickian transport due to the long-term competition between the strong channeling and sequestration is reflected by the non-zero skewness and kurtosis ( Fig.…”
Section: Influence Of Hydrofacies Properties On Plume Snapshots and Ssupporting
confidence: 82%
“…The mechanism of transport in either the alluvial settings or the fracture/matrix system (simplified by a dual-porosity model) can be described by random-walking particles whose waiting time distribution is controlled by the non-flowing portions [16]. It is therefore expected that the above methods, such as the TSM and the CTRW framework, may capture complex transport in fractured media at various scales, as demonstrated in [19,71,103]. In alluvial settings, the particle waiting time distribution is affected by the molecular diffusion coefficient and the thickness of the host floodplain layer.…”
Section: Other Transport Theories For Non-fickian Transportmentioning
confidence: 97%
“…For example, analyses show that the effective matrix diffusion coefficient may be scale dependent [40], permeability and porosity changes with support scale and spatial resolution [41], and apparent dispersivity in fractures varies with the scale of observation (in time and space) [7]. The extensive upscaling experiments conducted by Öhman et al [42] and Odén et al [43] further reveal that the standard continuum model cannot capture the dynamics of tracer transport through regional-scale, nonstationary fractured media.…”
Section: Previous Modeling Approaches and Limitationsmentioning
confidence: 99%
“…Characterization and modeling of groundwater flow and solute transport in fractured rocks has long been a challenging scientific task because of the strongly heterogeneous nature of the medium. Recent reviews of the approaches used are given, for example, by Öhman et al [2005], Oden et al [2008], and Neuman [2005]. Flow in heterogeneous systems gets channelized into pathways of least resistance.…”
Section: Introductionmentioning
confidence: 99%
“… Tsang and Neretnieks [1998] summarized results from a number of experimental and modeling studies that demonstrated the occurrence of flow channeling in fractured rocks. The typically anomalous breakthrough curves, characterized by fast early peak arrivals and long tails, can in many cases be explained by the occurrence of fast‐flowing channels interacting with the slow‐flowing/stagnant domains and the rock matrix [e.g., see Carrera et al , 1998; Moreno and Neretnieks , 1993; Shapiro , 2001; Oden et al , 2008]. The interaction can take place through several interfaces: the channel‐rock matrix interface, the channel‐stagnant zones interface, and stagnant zones‐rock matrix interface [ Bodin et al , 2003].…”
Section: Introductionmentioning
confidence: 99%